Production of lycopene from tomato waste using solid state fermentation - Jamal, Parveen; Haslamona, Ali; Jaswir, Irwandi; Akbar, Iqrah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Lycopene is a well-known carotenoid, causing the red color of fresh tomatoes. The significance of lycopene as antioxidant agent and coloring in the cosmetics, and its use in pharmaceutical and food industries has expanded in the recent years. Extraction of lycopene was improved effectively under solid state fermentation process; whereby, cellulase produced from the fermentation process was employed to degrade the cell-wall constituents, which facilitated the release of intracellular contents. The optimum conditions for the fermentation process were determined using response surface methodology (RSM). A face-centered central composite design (FCCCD) was employed to investigate the effects of three independent factors: moisture content, inoculums size and incubation time. Twenty experiments were conducted and each one was replicated (repeated) three times. The obtained data was analyzed using design expert software version 6. Regression analysis showed that 94.56% of the variation was explained by the software. Under optimized conditions the highest lycopene yield was 307.2µg/g when the moisture content was 80%, the inoculums size was 15% in 4 incubation days. The experimental values agreed with the predicted values, thus proving stability of the model used and the success of RSM. This study showed as to how fermentation can improve the extraction process by comparing the result with the control (extraction without fermentation) which was 0.8µg/g.